Contact-setting communikemes in the Komi language - Natalia I. Gulyaeva (Финно-угорский мир, 2022)
lntroduction. The article describes the contact-setting communikemes in the Komi language. The subject of the research is the implicit meanings and intentions of communicants transmitted by these syntactic units. The purpose of the work is to identify and describe the most common contact-establishing communikemes in the Komi language, their pragmatic specifics, and the features of functioning in speech.